SLPI is a critical mediator that controls PTH-induced bone formation - Akito Morimoto (Nature Portfolio, 2021)
The mechanism by which parathyroid hormone mediates the switch from bone resorption to bone formation is unclear. Here, the authors show that SLPI regulates the communication between osteoblasts and osteoclasts to promote the anabolic effect of parathyroid hormone.